Access to Physical Therapy for Pediatric and Adolescent Patients Following Orthopedic Surgery. (May 2019) - Sarkisova, Natalya; Smith, Ryan; VandenBerg, Curtis; Pace, J. Lee; Goldstein, Rachel Y.
The objective of this study was to evaluate the relationship between insurance status and access to physical therapy (PT). Masked telephone interviews with PT facilities in a major metropolitan area were conducted with researchers posing as parents of children. Each facility was called twice: once with a private insurer and once with a government insurer. Earliest available appointment, if the facility accepted insurance, and amount of time required to return a call were recorded. Fifty-four PT clinics responded. Clinics that accepted private insurance were significantly greater than the proportion that accepted government insurance (85.2% vs 14.8%, P < .001). There was no significant difference in time between initial call and first offered appointment, in the 2 insurance conditions (private: 8.09 days, government: 8.67 days, P = .33). There were no significant differences in appointment delays between both insurance conditions. Our study found there was a significantly lower rate of children with government-funded insurance that had access to postsurgical rehabilitation.